中国城市软创新的时空演化及其影响因素 - Wang, Bangjuan; Liu, Chengliang; Mao, Weisheng; Li, Yuan (Dili Xuebao/Acta Geographica Sinica, 2025)
Trademarks increasingly serve as indicators of product innovation and broader industry shifts, encompassing a wide range of innovation activities and soft innovations often overlooked by patents. However, research on the relationship between trademarks and innovation remains in its early stages, with a lack of exploration into China's soft innovation from the trademark perspective. This paper addresses this gap by analyzing trademark data from 1980 to 2021. Integrating big data mining, statistical methods, GIS spatial analysis, and econometric models, it explores the spatio-temporal evolution patterns and factors influencing soft innovation in Chinese cities. The results find that: First, the scale of trademark applications exhibits a complex evolution characterized by continuous growth and fluctuation, showing a dual-cycle and three-stage trend. Soft innovation output in cities follows a stepwise spatial distribution pattern, decreasing from the eastern coastal areas to central and western regions. This pattern reflects a regional agglomeration, with hierarchical changes showing both stability and variability. Second, the distribution of trademark categories exhibits significant heterogeneity, notably with a continuous rise in the proportion of service categories. Subcategories are concentrated in the consumer goods sector and maintain steady growth. Spatially, these categories show a mix of clustering and dispersion, predominantly aligning with industrial development trends and innovation-driven features, presenting a pattern congruent with the industrial structure. Finally, factors such as the development of the internet, establishment of new enterprises, and technological innovation have a significant positive impact on trademark applications. Population size, GDP, and urban commodity exports also contribute significantly to increased trademark activity. The influence of industrial composition on trademark application intensity exhibits certain heterogeneity. There is a clear correlation between knowledge-intensive service industries and trademark activity, whereas a negative relationship is observed with government service departments.
Keywords: China; determinants; industrial structure; patents; regional innovation; trademarks